2020
DOI: 10.1038/s41408-020-00354-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing measures of hematologic response after high-dose melphalan and stem cell transplantation in AL amyloidosis

Abstract: Hematologic complete response (hemCR) in AL amyloidosis requires absence of monoclonal protein by immunofixation electrophoreses (IFE) and normal serum free light chain ratio (FLCR). Recent literature suggests that an involved free light chain (iFLC) <20 mg/L or difference in free light chains (dFLC) <10 mg/L may more accurately predict outcomes after treatment. We evaluated overall survival in 340 patients treated with high-dose melphalan and stem cell transplantation (SCT). Of 305 patients evaluable 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The size of the underlying PC clone at baseline affects prognosis 5 . Profound decreases of LC levels through PC-targeting chemotherapy can result in the improved organ dysfunction and arrest the otherwise inexorable progression of the disease 6 10 . After treatment, even small increases in amyloid LCs can cause organ progression and reduced survival 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The size of the underlying PC clone at baseline affects prognosis 5 . Profound decreases of LC levels through PC-targeting chemotherapy can result in the improved organ dysfunction and arrest the otherwise inexorable progression of the disease 6 10 . After treatment, even small increases in amyloid LCs can cause organ progression and reduced survival 11 .…”
Section: Introductionmentioning
confidence: 99%
“…We and others recently re-assessed the definition of the conventional hematological CR definition. [14][15][16] In these studies, both the ratio) were found to be important from survival standpoint. [14][15][16] However, the quantitative light chain component (expressed as iFLC < 20 mg/L or dFLC < 10 mg/L) directly impacts the organ dys- 17 and marrow MRD assessment.…”
Section: Discussionmentioning
confidence: 90%
“…[14][15][16] In these studies, both the ratio) were found to be important from survival standpoint. [14][15][16] However, the quantitative light chain component (expressed as iFLC < 20 mg/L or dFLC < 10 mg/L) directly impacts the organ dys- 17 and marrow MRD assessment. 8,[18][19][20][21][22] Alternatively, better ways to predict delayed CR among deep responders, using baseline immunologic, or genetic profiling and at EOT should also be explored.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations